Effect of resolvins on sensitisation of TRPV1 and visceral hypersensitivity in IBS. Issue 7 (6th October 2020) - Perna, Eluisa; Aguilera-Lizarraga, Javier; Florens, Morgane V; Jain, Piyush; Theofanous, Stavroula A; Hanning, Nikita; De Man, Joris G; Berg, Maya; De Winter, Benedicte; Alpizar, Yeranddy A; Talavera, Karel; Vanden Berghe, Pieter; et al.
Abstract : Objective: Resolvins (RvD1, RvD2 and RvE1) are endogenous anti-inflammatory lipid mediators that display potent analgesic properties in somatic pain by modulating transient receptor potential vanilloid 1 (TRPV1) activation. To what extent these molecules could also have a beneficial effect on TRPV1 sensitisation and visceral hypersensitivity (VHS), mechanisms involved in IBS, remains unknown. Design: The effect of RvD1, RvD2 and RvE1 on TRPV1 activation and sensitisation by histamine or IBS supernatants was assessed on murine dorsal root ganglion (DRG) neurons using live Ca 2+ imaging. Based on the results obtained in vitro, we further studied the effect of RvD2 in vivo using a murine model of post-infectious IBS and a rat model of post-inflammatory VHS. Finally, we also tested the effect of RvD2 on submucosal neurons in rectal biopsies of patients with IBS. Results: RvD1, RvD2 and RvE1 prevented histamine-induced TRPV1 sensitisation in DRG neurons at doses devoid of an analgesic effect. Of note, RvD2 also reversed TRPV1 sensitisation by histamine and IBS supernatant. This effect was blocked by the G protein receptor 18 (GPR18) antagonist O-1918 (3–30 µM) and by pertussis toxin. In addition, RvD2 reduced the capsaicin-induced Ca 2+ response of rectal submucosal neurons of patients with IBS. Finally, treatment with RvD2 normalised pain responses to colorectal distention in both preclinical models of VHS. Conclusions: Our data suggest that RvD2 and GPR18 agonists may represent interesting novel compounds to be further evaluated as treatment for IBS.